Quorum sensing and quorum quenching abilities of selected bacteria isolated from antarctic / See-Too Wah Seng - See-Too, Wah Seng (2013)

(untitled)
Quorum sensing (QS) is a phenomenon which refers to bacterial cell-to-cell communication in a population manner. QS regulates diverse activities in bacteria. Bacteria that possess QS activity communicate through secreted signal molecules or autoinducer. The Gram-negative bacteria and archaeon use acyl homoserine lactones (AHLs) as a QS signal to achieve regulation through the luxI-luxR homolog system, wheareas Gram-positive bacteria use small peptides as autoinducers. Some of the Proteobacteria use quinolone compound as signaling molecules. Quorum quenching (QQ) on the other hand refers to interference of QS that inactivates the signaling molecules.